METHOD FOR EVALUATING THE ASTROMETRIC AND PHOTOMETRIC CHARACTERISTICS OF COMMERCIAL SCANNERS IN THEIR APPLICATION FOR THE SCIENTIFIC PURPOSE - Protsyuk, Yu. I.; Andruk, V. N.; Muminov, M. M.; Yuldoshev, Q. X.; Ehgamberdiev, Sh. A.; Eglitis, I.; Eglite, M.; Kovylianska, O. E.; Golovnya, V. V.; Kazantseva, L. V.; Kashuba, S. G. (Одеські астрономічні публікації, 2014)
Method for estimating the accuracy of astrometric (rectangular coordinates) and photometric (diameters and magnitudes) characteristics of commercial scanners is proposed and applied. The method is demonstrated using an example of processing of sequential scans of plates, which were exposed with different telescopes and then digitized with resolution of 1200 dpi with several Epson scanners. Scanning operations were carried out in various observatories as part of development of the database of photographic observations for Virtual Observatories (Vavilova, 2012). Errors of studied scanners are equal to σx, y = ± 0.02-0.06px and σm = ± 0.015-0.024 mag for astrometry and photometry, respectively.